Shape and sizing optimisation of automotive structures with deterministic and probabilistic design constraints. (15th November 2010) - Rais-Rohani, Masoud; Solanki, Kiran N.; Acar, Erdem; Eamon, Christopher D.
This paper presents the results of a study on the combined shape and sizing optimisation of automotive structures while examining the effects of different design constraints and associated uncertainties on reliability and efficiency of the optimum designs. Nonlinear transient dynamic finite element analysis is used for full- and offset-frontal crash simulations of a full vehicle model. Surrogate models are developed for the intrusion distance and peak acceleration responses at different vehicle locations based on the material and geometric characteristics of the rail component. The obtained solutions provide insight on the effect of uncertainties in optimum design of automotive structures.